THE ROLE OF INNOVATIVE TECHNOLOGIES IN THE EDUCATIONAL PROCESS. - N.A.USMANOVA (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article describes the stages of development of the education system, methods, the education system of developed countries, the role of international assessment programs in education, teaching processes and their pedagocical basis.